FDR and the Spanish Civil War : Neutrality and Commitment in the Struggle that Divided America - Tierney, Dominic, 1977- (Book collections on Project MUSE., 2007)
Provides new understanding of Franklin Roosevelt's involvement in the Spanish Civil War, claiming that he was activist and pro-Loyalist.